2012
DOI: 10.1007/s00586-012-2230-2
|View full text |Cite
|
Sign up to set email alerts
|

“In situ” fusion or reduction in high-grade high dysplastic developmental spondylolisthesis (HDSS)

Abstract: Purpose To assess if the evaluation of the spino-pelvic balance can be effective in the surgical decision making of the high-grade high dysplastic developmental spondylolisthesis (HDDS). Methods Sixteen patients affected with high-grade HDDS (6 treated with ''in situ'' fusion, and 10 with reduction and fusion) were retrospectively evaluated. A clinical and radiological assessment of the deformity correction was carried out, with a minimum follow-up of 2 years. The differences between the pre-and postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 25 publications
3
30
0
3
Order By: Relevance
“…This has contributed to the correction of the patients' clinical deformity and therefore the overall spinal balance which in turn may decrease adjacent level disease in the future. These improvements follow other published data 7,13 . In this case series the fusion was always extended to LV4 vertebra.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This has contributed to the correction of the patients' clinical deformity and therefore the overall spinal balance which in turn may decrease adjacent level disease in the future. These improvements follow other published data 7,13 . In this case series the fusion was always extended to LV4 vertebra.…”
Section: Discussionsupporting
confidence: 91%
“…In-between, partial reductions and trans-sacral fixation using screws or fibular allografts have also been suggested 8,24,26 . Although the concept of reducing spinal deformity before fusion is attractive, the issue of surgical reduction versus in situ fusion remains controversial 13,16,19,27 . Harms and Jeszenszky 3 suggested a modification of the traditional PLIF that involved the placement of bone graft and titanium mesh cages, via a transforaminal route (TLIF), into the disc space that had previously been distracted using pedicle screw instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Although in situ fusion is an effective treatment for lower grades of pediatric spondylolisthesis, studies have reported that this technique results in a high rate of pseudarthrosis, slip progression, and persistent cosmetic deformity in HDDS patients. 2,20 In patients with HDDS treated using in situ fusion, adjacent mobile segments in the upper lumbar spine, pelvis orientation, and thoracic spine compensate for the local sagittal imbalance of the lumbosacral junction. The result is a suboptimal, but satisfactory global sagittal balance of the trunk, even in the most severe grade of slipping.…”
Section: Discussionmentioning
confidence: 99%
“…Lamartina also introduced the concepts of Severity Index and Unstable Zone that could be always defined and studied, when surgeons decide to treat this kind of listhesis. Other authors [12][13][14][15][16] proposed postero-lateral fusion only, even without decompression [17,18], as surgical treatment, showing relative good results, in their series.…”
Section: Introductionmentioning
confidence: 97%